2005
DOI: 10.1002/jsfa.2321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐pressure and traditional thermal processing of tomato purée on carotenoids, vitamin C and antioxidant activity

Abstract: Bioactive compounds (carotenoids and vitamin C) and 2,2-diphenyl-1-picrylhydrazyl radical (DPPH • ) scavenging activity [50% depletion of initial DPPH • radical (EC 50 ) and antiradical efficiency (AE)], in aqueous (AQ) and organic (OR) fractions, were measured in tomato purée subjected to high-pressure (HP) (400 MPa/25 • C/15 min), low pasteurisation (LPT) (70 • C/30 s), high pasteurisation (HPT) (90 • C/1 min), freezing (F) (−38 • C/15 min), and HPT plus F (HPT + F).In addition, physical and physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(120 citation statements)
references
References 39 publications
12
102
0
6
Order By: Relevance
“…Some authors, nevertheless, have reported that processing had no significant effect on the carotenoid profile (Lee and Coates, 2003;Vervoort et al, 2011). Also, there were no significant changes after thermal treatment in a study by Sanchez-Moreno et al (2005), after HPP treatment by Donsi et al (1996) and Esteve et al (2009) Ultra-High Temperature processed 6.1 6.2 * Consumer Acceptance Testing (n = 14); 9 point hedonic scale-9 = like extremely; 8 = like very much; 7 = like moderately; 6 = like slightly; 5 = neither like nor dislike; 4 = dislike slightly; 3 = dislike moderately; 2 = dislike very much; and 1 = dislike extremely.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors, nevertheless, have reported that processing had no significant effect on the carotenoid profile (Lee and Coates, 2003;Vervoort et al, 2011). Also, there were no significant changes after thermal treatment in a study by Sanchez-Moreno et al (2005), after HPP treatment by Donsi et al (1996) and Esteve et al (2009) Ultra-High Temperature processed 6.1 6.2 * Consumer Acceptance Testing (n = 14); 9 point hedonic scale-9 = like extremely; 8 = like very much; 7 = like moderately; 6 = like slightly; 5 = neither like nor dislike; 4 = dislike slightly; 3 = dislike moderately; 2 = dislike very much; and 1 = dislike extremely.…”
Section: Discussionmentioning
confidence: 88%
“…En general, la capacidad antioxidante de los zumos de frutas se relaciona con la composición y la concentración de compuestos bioactivos tales como vitaminas, fenoles, carotenoides o flavonoides (Sánchez et al, 2006). Takeoka et al (2001) reportan que la vitamina C y los fenoles son los principales componentes antioxidantes en zumos de frutas.…”
Section: Análisis De La Concentración De Carotenoidesunclassified
“…Improving new preservation techniques are also important to maintain food freshness and guarantee stability of bioactive compounds with minimum physical and chemical processes [41,59,[60][61][62][63][64]. Moreover, some researches demonstrated that bioactive properties of fresh fruit juices are maintained better after PEF application [41,59,[60][61][62][63][64].…”
Section: Effects Of Pef On Bioactive Properties and Bioavailabilitymentioning
confidence: 99%